Formulation and Effectiveness Test of 96% Ethanol Extract Anti-Acne Serum Cashew Leaves (Anacardium occidentale L.) - Mc Seer, Raysha; Rini Dwiastuti; Eka Indra Setyawan (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Recently, the use of cosmetics to cure acne made from natural ingredients can have a good effect. Cosmetic preparations that are currently developing rapidly are serum preparations because they have better effects, and the moisturizing technology used is based on skin physiology. The natural ingredient in question is cashew leaves, which treat acne caused by Propionibacterium acnes. This research aims to obtain a serum preparation of cashew leaf extract to determine its effectiveness against P. acne and optimize the two ingredients, namely carbopol and triethanolamine (TEA) so that the serum preparation has physical stability that meets predetermined standards. Methods: This research is pure experimental research of a qualitative nature to obtain a serum preparation of cashew leaf extract with effectiveness as an anti-acne and using the factorial design method with the optimization factor for carbopol concentration comparison as a gelling agent and TEA as an alkalizing agent. The physical property parameters observed as a response to the equation are spreadability and viscosity using two-way statistical tests, ANOVA, with IBM SPSS statistics 29.0.1.0 software. Results: The research results obtained indicate the effectiveness of cashew leaf extract serum preparations against bacteria, such as Propionibacterium acnes. Apart from that, there is no significant difference between the formulas in the spreadability parameters, which means there is no influence from variations in carbopol and TEA concentrations on the physical evaluation of spreadability. Meanwhile, there are significant differences between the formulas in the viscosity parameters, there is an influence of variations in the concentration of carbopol and TEA on the physical evaluation of viscosity. Conclusion: Cashew leaf extract serum preparations are effective in treating bacteria Propionibacterium acnes, the cause of acne.